THE DISCURSIVE CONSTRUCTION OF KPK (CORRUPTION ERADICATION COMMISSION) AND POLRI (INDONESIAN NATIONAL POLICE) IN THE JAKARTA POST: A DISCOURSE-HISTORICAL APPROACH - Renaldy, Rendy (2016)
This study investigates discursive construction employed by the Jakarta Post in the news of KPK and Polri through nomination and predication strategies of Discourse-Historical Approach (DHA) proposed by Reisigl and Wodak (2001). KPK (Corruption Eradication Commission) is a government agency established to fight corruption, meanwhile Polri is Indonesian National Police. This study uses descriptive qualitative method to analyze five news articles about KPK and Polri. The aim of the study is to identify how social actors in the related news articles are referred to and predicated by the Jakarta Post. The findings reveal two main points. First, proper name is the most frequent linguistic device in nomination strategies used by the Jakarta Post in referring to social actors of KPK and Polri issues. Second, explicit predicate is the most frequent predication strategies employed by the Jakarta Post in representing social actors of KPK and Polri issues. Both of these strategies are used by the Jakarta Post to portray the image of Abraham Samad and Bambang Widjojanto who are from KPK as positive while Budi Gunawan who is from Polri as the negative one. In addition, this study also finds that by using nomination and predication strategies, the Jakarta Post expresses its political standpoint to support anticorruption movement. Keywords: KPK, Polri, Discourse-Historical Approach (DHA), Nomination Strategies, Predication Strategies